2020
DOI: 10.1039/c9ew00859d
|View full text |Cite
|
Sign up to set email alerts
|

Organic structure and solid characteristics determine reactivity of phenolic compounds with synthetic and reclaimed manganese oxides

Abstract: Phenolic substituents and manganese oxide characteristics influence oxidation kinetics and mechanism, as well as the utility of QSARs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 61 publications
1
48
0
Order By: Relevance
“…With the exception of Mg 2+ with triclosan described above, we observe the same trend in cation co‐solute suppression regardless of the phenol, even though transformation rates vary greatly (i.e., pseudo‐first‐order rate constants for phenols oxidized by birnessite with Na + in solution range from 0.02 to 0.27 min −1 ) (Figure 1; Supplemental Table S2). This large range in reaction rates is attributable to the varying structures of the four phenols (Supplemental Figure S1), which leads to changes in oxidation rate similar to the trend seen here (Arnold et al., 2017; Trainer et al., 2020; Tratnyek, Weber, & Schwarzenbach, 2003). Despite this wide range in reaction rates, the oxidation rate constants of phenols under all conditions, except for Mg 2+ with triclosan, follow the order of BPA > p ‐cresol > estrone > triclosan.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…With the exception of Mg 2+ with triclosan described above, we observe the same trend in cation co‐solute suppression regardless of the phenol, even though transformation rates vary greatly (i.e., pseudo‐first‐order rate constants for phenols oxidized by birnessite with Na + in solution range from 0.02 to 0.27 min −1 ) (Figure 1; Supplemental Table S2). This large range in reaction rates is attributable to the varying structures of the four phenols (Supplemental Figure S1), which leads to changes in oxidation rate similar to the trend seen here (Arnold et al., 2017; Trainer et al., 2020; Tratnyek, Weber, & Schwarzenbach, 2003). Despite this wide range in reaction rates, the oxidation rate constants of phenols under all conditions, except for Mg 2+ with triclosan, follow the order of BPA > p ‐cresol > estrone > triclosan.…”
Section: Resultssupporting
confidence: 64%
“…Sorption to the manganese oxide surface is the first step in BPA oxidation, followed by electron transfer and diffusion of products from the surface (Stone, 1987). The mechanism for BPA oxidation is electron transfer limited, meaning that the sorption process is faster than the electron transfer (Trainer et al., 2020). Percent sorption was calculated by the difference in BPA concentration in solution (i.e., determined by filtration) and total BPA concentration (i.e., determined by dissolution of manganese oxide).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rate constants for the dehalogenation of polybrominated diphenyl ethers (PBDE) and polychlorinated biphenyl (PCBs) by nano zero-valent iron (nZVI) ranged from 0.0001 to 0.1 h –1 . , Bokare et al determined that the rate constant for the reaction between TCS and nZVI was around 0.04 h –1 , which could be further accelerated by doping of palladium. Trainer et al found that rate constants for the oxidation of phenol compounds by manganese oxide (δ-MnO 2 ) ranged from 0.001 to 149 h –1 with a value of 7.6 h –1 for TCS. The relatively lower reaction rate constants for TCS in this study are primarily because the concentration of a-BC and associated electrons were much lower than the metals.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the oxidation rate of phenolic compounds varies among manganese oxide phases, the greater abundance of the phyllomanganate structure may explain why the geomedia reactivity was only partially restored by KMnO 4 treatment. In this study, we chose bisphenol A as a representative compound; however, different organic compounds have different rate-determining steps in reactions with manganese oxide, and additional research is needed to assess how the rates of different reaction mechanisms are impacted by the mineral phase, particularly after regeneration.…”
Section: Resultsmentioning
confidence: 99%